2019
DOI: 10.1080/21691401.2019.1596944
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA ANRIL protects against oxygen and glucose deprivation (OGD)-induced injury in PC-12 cells: potential role in ischaemic stroke

Abstract: lncRNA ANRIL was reported to be closely related to ischaemic stroke (IS). In this study, we used oxygen-glucose deprivation (OGD) to stimulate rat adrenal medulla-derived pheochromocytoma cell line PC-12 to construct an in vitro IS cell model and investigated the role of ANRIL and the underlying mechanism. PC-12 cells were stimulated by OGD and/or transfected with pc-ANRIL, si-ANRIL, miR-127 mimic, miR-127 inhibitor, pEX-Mcl-1, sh-Mcl-1 and their negative controls. Cell viability, apoptosis, mRNA and protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…38 Growing literature has shown that down-regulation of lncRNAs is implicated in the pathological process of IS, such as lncRNA Oprm1, 39 lncRNA ZFAS1 40 and lncRNA ANRIL. 34 Coincident with expression trend of previous studies, we also observed that SNHG7 was down-regulated by MCAO treatment in brain tissues of mice and by OGD/R treatment in PC12 cells, implying that SNHG7 might involve in the pathologies of IS. Besides, numerous studies have revealed the key role of SNHG7 in many diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…38 Growing literature has shown that down-regulation of lncRNAs is implicated in the pathological process of IS, such as lncRNA Oprm1, 39 lncRNA ZFAS1 40 and lncRNA ANRIL. 34 Coincident with expression trend of previous studies, we also observed that SNHG7 was down-regulated by MCAO treatment in brain tissues of mice and by OGD/R treatment in PC12 cells, implying that SNHG7 might involve in the pathologies of IS. Besides, numerous studies have revealed the key role of SNHG7 in many diseases.…”
Section: Discussionsupporting
confidence: 89%
“…A rat adrenal pheochromocytoma cell line PC12 with specific characteristic of neural cells was used in accordance with previous studies. [33][34][35][36] PC12 cells were bought from American Type Culture Collection (ATCC, USA). PC12 cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin and incubated at 37°C under a humidified atmosphere with 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…Moreover, circulating leukocytes exhibit cerebral ischemia-induced changes in the RNA expression profile detectable in circulating blood, as demonstrated in a series of animal models of IS (Tang et al, 2001; Sharp et al, 2011; Dagonnier et al, 2018; Li et al, 2019). Although emerging studies have shown that numerous lncRNAs may be involved in the regulation of IS pathophysiologic processes (Dykstra-Aiello et al, 2016; Wu et al, 2017; Zhang et al, 2018; Liu et al, 2019; Zhu et al, 2019), their roles in the pathological mechanisms, nosogenesis and progression of IS still need to be further clarified (Beermann et al, 2016). In the present study, we used high-throughput sequencing technologies to generate a signature profile of numerous lncRNAs and mRNAs in AIS compared with matched healthy controls, and bioinformatics analysis was performed to analyze the data.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous researchers have shown great interest in exploring the association between lncRNA profiles and neurological disorders (Wu et al, 2013; Dykstra-Aiello et al, 2016; He et al, 2018). Importantly, an increasing number of studies have shown that lncRNAs play crucial roles in the pathogenesis of IS (Dykstra-Aiello et al, 2016; Liu et al, 2019). Although the functions of most lncRNAs in neuroprotection and IS remain to be clarified (Dharap et al, 2012), RNA-Seq analyses have indicated that the abnormal expression of lncRNAs is closely associated with IS, and increasing evidence has confirmed that lncRNAs generally contribute to the development and progression of IS as well as to recovery from IS (Bhattarai et al, 2017; Guo et al, 2017; Wang et al, 2017; Zhang et al, 2018; Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation